Prevalence of Schistosoma mono- and co-infections with multiple common parasites and associated risk factors and morbidity profile among adults in the Taabo health and demographic surveillance system, South-Central Côte d'Ivoire - Fidèle K. Bassa; Ikenna C. Eze; Rufin K. Assaré; Clémence Essé; Siaka Koné; Félix Acka; Véronique Laubhouet-Koffi; Dinard Kouassi; Bassirou Bonfoh; Jürg Utzinger; Eliézer K. N'Goran (BMC, 2022)
Abstract Background Schistosomiasis remains an important public health problem, also among adults, and infected individuals not treated serve as a reservoir for continued transmission. Despite this fact, evidence on the epidemiology of schistosomiasis in adults in Côte d'Ivoire is scanty. This study aimed to determine the prevalence and risk factors of Schistosoma infection and co-infection with other helminth species and Plasmodium among adults in the Taabo region in the south-central part of Côte d'Ivoire. Methods A cross-sectional survey was carried out in April and May 2017 in the frame of the "Côte d'Ivoire Dual Burden of Disease Study" (CoDuBu). A total of 901 randomly selected individuals, aged 18-90 years, provided blood, stool and urine samples for the diagnosis of malaria and helminth infections. Stool samples were subjected to the Kato-Katz technique for detection of Schistosoma mansoni and soil-transmitted helminth eggs, while urine samples were examined for eggs of Schistosoma haematobium and circulating cathodic antigen of S. mansoni. Risk factors and morbidity profiles were assessed using health examination and questionnaires. Multinomial logistic regressions were employed to identify risk factors and morbidity patterns associated with S. mansoni mono- and co-infections. Results The prevalence of S. mansoni and S. haematobium was 23.2% and 1.0%, respectively. Most S. mansoni were mono-infections (81.3%). Independent determinants of S. mansoni infection were young age, low socioeconomic status (mono- and co-infection) and poor hygiene practices (co-infection) (P < 0.05). S. mansoni infection was independently associated with higher pain and symptom scores (mono-infection), poor self-rated health and low healthcare use (co-infection) (P < 0.05). Conclusions This study showed that adults represent a substantial reservoir of S. mansoni. To sustain schistosomiasis control and improve people's wellbeing, it is important to expand preventive chemotherapy from school-aged children to adults, coupled with hygiene and health education.